COVID-19 pandemic, Piacenza calling. The survival strategy of an Italian Emergency Department. - Poggiali, Erika; Vercelli, Andrea; Mazzoni, Silvana; Bastoni, Davide; Iannicelli, Teresa; Demichele, Elena; Ioannilli, Eva; Magnacavallo, Andrea (Acta Biomedica Atenei Parmensis, 2020)
CoVID-19 is a global health emergency, which has paralyzed most of the worldwide health systems. Italy is struggling hard with CoVID-19 pandemic since the end of February 2020, to avoid the collapse of its health  system. The number of CoVID-19 patients and deaths are increasing day by day. At time of writing, in Italy there are 102253 infected patients and 19899 deaths. Despite being a relatively small city, Piacenza is one of the epicentres of the Italian epidemic, and our own hospital – Guglielmo da Saliceto – has quickly become a “CoVID-19 hospital”. Fully 80% of beds in our hospital are reserved for ill CoVID-19 patients and ICU has tripled the number of beds. All these changes have required a great effort for all the medical staff to avoid the collpase of the local health system. We struggled to maintain our normal standard of care for each patient, but the severity of the disease and the high number of critically ill patients frustrated our efforts. Here we report our experience and challenge with managing such a disaster. We hope it could be useful for other Emergency Departments trapped in this global pandemic.